Aerobic Games and Playful exercises in 9-YearOld Boys: Intensity and Fitness Effects - Gunnar E Mathisen; Rein M Jensen; Svein A Pettersen (University of Maribor Press, 2016)
Previous research on exercise for pre-adolescents with the purpose of improving aerobic fitness levels has yielded contradictory results. Sufficient training intensity, frequency and duration are the crucial factors in achieving this goal; the question, however, is whether it is possible to reach sufficient intensity levels using aerobic games and playful exercises. Variety and fun are the important factors in motivating children to participate in physical exercises and sports. Therefore, the aim of the study was to investigate the effect of high intensity exercises in pre-adolescent boys, using programs consisting of fun activities and aerobic games. The findings show that the participants achieved intensity levels above 80 % of HRpeak on average in about 60 % of the total exercise time, resulting in significantly improved aerobic fitness.